Pemanfaatan Media Lagu untuk Meningkatkan Konsentrasi Belajar Siswa Kelas I Sekolah Dasar Negeri Sukajadi Haurgeulis - Inayatun Nabillah; Wiena Safitri; Alfi Satria (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
Education is a conscious and planned pedagogical effort to develop students in various aspects of life. And teacher plays a significant role in the educational process to create a conducive classroom atmosphere which greatly affects student learning outcomes. Concentration is a key for students in learning, and in oder to improve students focus to study, it is necessary to use learning media of song or music. During the teaching practice at primary school of Sukajadi Haurgeulis, the researcher observed and recognized that the first-grade students were less conducive. They often run and played around and also had less attention to teacher. The students got involved more with their classmates. Therefore, the teacher is required to modify the learning process to foster better and enjoyful learning activities which lead to learning enthusiasm. The study aims to explore the use of song as learning media in the classroom and to find out whether the media can improve student concentration. The study uses a descriptive qualitative approach through data collection of observation, interviews, and documentation to gather information and data. The study shows that the use of song learning media affects and increases student engagement. The song offers several benefits, such as students motivation enhancement, and the improvement of memory retention and learning focus. Songs are played in three different purposes involving the classroom introduction phase, student readiness check, and introduction of the alphabet lesson topic. The positive impacts resulted in the study are as follow better students’ attention during lessons, student concentration improvement, and simple comprehension of learning topic and many more dynamic learning creation.